Analytical study on the behaviour of composite space truss structures with openings in a concrete slab - Sangeetha, Palanivelu (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A space truss structural system is a three-dimensional arrangement of linear elements in a pyramid pattern forming a Double Layer Grid (DLG) system. Space trusses are an elegant and economical means of covering larger areas such as roof systems, in a wide variety of applications such as a stadium, aircraft-hanger, assembly hall, etc.
Keywords: composite structures; space truss; slab openings; maximum load; maximum deflection; ANSYS; konstrukcje kompozytowe; kratownice przestrzenne; płyty; maksymalne obciążenie; ugięcie